Enhanced bioenergy recovery and nutrient removal from swine wastewater using an airlift-type photosynthetic microbial fuel cell. (1st July 2021) - Li, Ming; Zhou, Minghua; Tian, Xiaoyu; Tan, Chaolin; Gu, Tingyue
Abstract: Swine wastewater (SW) was used herein as the substrate in an airlift-type photosynthetic microbial fuel cell (APMFC) for power generation, and also, after anode pre-treatment, as a medium for Chlorella vulgaris cultivation in the cathode compartment accompanied with CO2 biofixation. Compared to heterotrophic cultivation, APMFC under mixotrophic cultivation showed a better performance in biomass yield, lipid accumulation and power generation. The highest chemical oxygen demand (COD) removal (96.3%), total organic carbon (TOC) removal (95.1%), NH4 + -N removal (99.1%), and total phosphorus (TP) removal (98.9%) were achieved using 2-fold diluted SW. In APMFC (SW of 2-fold dilution), the highest CO2 biofixation rate and lipid productivity reached 1149 mg L −1  d −1 and 164 mg L −1  d −1, respectively. Ammonium migration from the anodic compartment to the cathodic compartment gradually increased as the ammonium concentration increased in the anolyte. The energy balance analysis suggested that the highest net energy output reached 1.92 kWh m −3 in APMFC fed with 2-fold diluted SW, which showed a superiority in clean energy production. Microbial community analysis indicated that the electrogenic microorganisms were further enriched in the anodic biofilm, which could enhance the power generation. This study provided a promising way for simultaneous SW treatment, CO2 biofixation and bioenergy generation. Highlights: An airlift photosynthetic MFC using swine wastewater as substrate was developed. APMFC performed better in mixotrophic cultivation and enriched electricigens. A net energy of 1.92 kWh m −3 with high COD, NH4 + -N and TP removal were achieved. NH4 + -N migration between two chambers increased with NH4 + -N in the anolyte. It was attractive for SW treatment, CO2 biofixation and bioenergy generation.